Combined Effect of Pelvic Proprioceptive Neuromuscular Facilitation and Core Strengthening on Trunk Control, Balance, and Gait in Individuals with Paraplegia (International Journal of Physiotherapy, 2023)
Background: Paraplegia causes substantially reduced motor and sensory functions in the lower limbs and insufficient control over the trunk and pelvis. Regulating one’s trunk and pelvis is essential for balance and gait. However, among people with paraplegia, poor trunk and pelvic control is a crucial risk factor for immobility and a worsened quality of life (QoL). Despite conventional methods for enhancing trunk and pelvic control, there is a lack of standardized techniques to improve trunk and pelvic control for SCI patients. So, the present study aims to evaluate the combined effects of pelvic proprioceptive neuromuscular facilitation and core strengthening on trunk control, balance, and gait in paraplegic patients.Methods: A quasi-experimental study involving 17 participants (13 males, 4 females) with subacute paraplegia having the neurological level of injury (T6-T12) with ASIA Impairment Scale (ISNCSCI) grades B and C. Intervention was given to the participants for 45 minutes per session, five times/week for four weeks. Before and after the intervention, the participant’s performance was assessed using the trunk control test for SCI, the Berg Balance Scale, the SCI-FAI, and the Walking Index for Spinal Cord Injury II (WISCI).Results: After four weeks of intervention, the comparison between the pre-and post-intervention outcomes of the Trunk Control Test (p=0.001), BBS (p=0.001), SCI-FAI (p=0.001), and WISCI (p=0.001) showed significant differences.Conclusion: The current study concluded that pelvic PNF combined with core strengthening effectively improved trunk control, balance, and gait in subacute paraplegic patients. Both interventions are safe to perform.